Connections, Information and Reality: Thinking about the internet of things - Ben Van Lier (Journal of Systemics, Cybernetics and Informatics, 2011)

(untitled)
The number of connections between people, organizations and technology is proliferating rapidly, and the amount of information they produce, exchange and share is increasing accordingly. These connections and the information they produce are defining and shaping our daily life and work and our perception of reality. Computers in all forms are becoming smaller and less visible, but they are omnipresent. This development of information technology ‘everyware’, as Greenfield calls it, is also referred to as ubiquitous computing. With the development of ubiquitous computing, computers not only disappear from our perception, but also from our experience. When these new and almost invisible technological devices are tied together, for instance in the Internet of Things, the information resulting from that connection will be more than the sum of its parts. The Internet is the place where subjects are connected and where they exchange and share information. With the development of the ‘Internet of things’, the Internet will also connect objects and enable them to exchange and share information. In this Internet of the future, subjects and objects are more and more connected in random coalitions and networks on the basis of information. These new connections and their seamless exchanging and sharing of information will challenge traditional organizational structures. The information produced in networks will be used for changes to our existing reality and will help create a new reality. Will this development of subjects and objects connected in networks raise new questions and challenges for science and for the development of knowledge within a changing reality?